Challenges Faced By Counselors In Pakistani Universities - Sain, Zohaib Hassan; Sain, Shahzadi Hina (Universitas Islam Bunga Bangsa Cirebon, 2024)
The presence of counselling services in Pakistani universities is pivotal for the maintenance of student's mental health and academic prosperity. However, these services are challenged by various factors. This study seeks to delve into the cultural, institutional, and professional barriers that impede the efficacy of these services. The research design employed a qualitative approach, using semi-structured interviews with university counsellors and administrative personnel and document analysis to gather data. The study's findings reveal that widespread cultural stigma, insufficient institutional resources, and limited professional development opportunities are significant hurdles to effective counselling. Furthermore, the study elucidates the adverse impact of unsupportive administrative policies on service provision. These challenges underscore the necessity for holistic strategies to enhance counselling services, such as increased institutional backing, enhanced counsellor training, and targeted awareness initiatives to combat stigma. Addressing these issues is imperative to foster a supportive environment that promotes student well-being and academic accomplishment. The implications of this study hold substantial significance for policymakers, university administrations, and mental health professionals striving to elevate the quality and accessibility of counselling services in higher education.